Molecular Mechanisms of Preeclampsia - N. Vitoratos; D. Hassiakos; C. Iavazzo (Hindawi Limited, 2012)
Preeclampsia is one of the leading causes of maternal morbidity/mortality. The pathogenesis of preeclampsia is still under investigation. The aim of this paper is to present the molecular mechanisms implicating in the pathway leading to preeclampsia.